Impact of age on the association between cardiac high-energy phosphate metabolism and cardiac power in women. Issue 2 (12th June 2017) - Nathania, Maria; Hollingsworth, Kieren G; Bates, Matthew; Eggett, Christopher; Trenell, Michael I; Velicki, Lazar; Seferovic, Petar M; MacGowan, Guy A; Turnbull, Doug M; Jakovljevic, Djordje G
Abstract : Objective: Diminished cardiac high-energy phosphate metabolism (phosphocreatine-to-ATP (PCr:ATP) ratio) and cardiac power with age may play an important roles in development of cardiac dysfunction and heart failure. The study defines the impact of age on PCr:ATP ratio and cardiac power and their relationship. Methods: Thirty-five healthy women (young≤50 years, n=20; and old≥60 years, n=15) underwent cardiac MRI with 31 P spectroscopy to assess PCr:ATP ratio and performed maximal graded cardiopulmonary exercise testing with simultaneous gas-exchange and central haemodynamic measurements. Peak cardiac power output, as the best measure of pumping capability and performance of the heart, was calculated as the product of peak exercise cardiac output and mean arterial blood pressure. Results: PCr:ATP ratio was significantly lower in old compared with young age group (1.92±0.48 vs 2.29±0.55, p=0.03), as were peak cardiac power output (3.35±0.73 vs 4.14±0.81W, p=0.01), diastolic function (ie, early-to-late diastolic filling ratio, 1.33±0.54 vs 3.07±1.84, p<0.01) and peak exercise oxygen consumption (1382.9±255.0 vs 1940.3±434.4 mL/min, p<0.01). Further analysis revealed that PCr:ATP ratio shows a significant positive relationship with early-to-late diastolic filling ratio (r=0.46, p=0.02), peak cardiac power output (r=0.44, p=0.02) and peak oxygen consumption (r=0.51, p=0.01). Conclusions: High-energy phosphate metabolism and peak power of the heart decline with age. Significant positive relationship between PCr:ATP ratio, early-to-late diastolic filling ratio and peak cardiac power output suggests that cardiac high-energy phosphate metabolism may be an important determinant of cardiac function and performance.